2013
DOI: 10.1242/jcs.130591
|View full text |Cite
|
Sign up to set email alerts
|

Arf activation at the Golgi is modulated by feed-forward stimulation of the exchange factor GBF1

Abstract: ADP-ribosylation factors (Arfs) play central roles in the regulation of vesicular trafficking through the Golgi. Arfs are activated at the Golgi membrane by guanine-nucleotide-exchange factors (GEFs) that are recruited from cytosol. Here, we describe a novel mechanism for the regulation of recruitment and activity of the ArfGEF Golgi-specific BFA resistance factor 1 (GBF1). Conditions that alter the cellular Arf-GDP:Arf-GTP ratio result in GBF1 recruitment. This recruitment of GBF1 occurs selectively on cis-Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 82 publications
2
22
0
Order By: Relevance
“… 46 , 48 Interestingly, GBF1 is also up-regulated in the present study, consistent with its recently reported role in responding to reduced ARF activity. 49 Taken together, these data suggest that ARFs merit future investigation as potentially important NMT substrates for the cytotoxic mode of action of NMT inhibitors. Arf1-targeted agents have recently been reported with potent in vivo anticancer activity, 50 and NMT inhibition is likely to result in a mechanistically distinct but functionally similar outcome by preventing Arf1 localization at the Golgi.…”
Section: Discussionmentioning
confidence: 84%
“… 46 , 48 Interestingly, GBF1 is also up-regulated in the present study, consistent with its recently reported role in responding to reduced ARF activity. 49 Taken together, these data suggest that ARFs merit future investigation as potentially important NMT substrates for the cytotoxic mode of action of NMT inhibitors. Arf1-targeted agents have recently been reported with potent in vivo anticancer activity, 50 and NMT inhibition is likely to result in a mechanistically distinct but functionally similar outcome by preventing Arf1 localization at the Golgi.…”
Section: Discussionmentioning
confidence: 84%
“…However, larval growth arrest after gbf-1(RNAi) in our screen precluded analysis. A recent study has suggested that GBF1 is recruited to membranes in response to increases in ARF-GDP (Quilty et al, 2014). We hypothesize that local changes in ratios of PA to PC species or decreases in DAG species, as seen in our studies of C. elegans microsomes, limit GBF1 recruitment and prevent generation of GTP-bound ARF1.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian GBF1 is a Rab1 effector [23] . Its cis -Golgi recruitment occurs in response to an increase in membrane-associated Arf-GDP [24] . The HDS1 domain of its S. cerevisiae homologue Gea1p was implicated in lipid droplet binding and Golgi recruitment [25] and in interaction with the early Golgi resident Gmh1p [26] .…”
Section: Introductionmentioning
confidence: 99%